Sporotrichoid-Like Spread of Cutaneous Mycobacterium chelonae in an Immunocompromised Patient - Daria Marley Kemp; Anusha G. Govind; Jun Kang; Caroline C. Brugger; Young C. Kauh (Hindawi Limited, 2017)
Mycobacterium chelonae is a rapidly growing mycobacterium found in water and soil that can cause local cutaneous infections in immunocompetent hosts but more frequently affects immunocompromised patients. Typically, patients will present with painful subcutaneous nodules of the joints or soft tissues from traumatic inoculation. However, exhibiting a sporotrichoid-like pattern of these nodules is uncommon. Herein, we report a case of sporotrichoid-like distribution of cutaneous Mycobacterium chelonae in a patient with systemic lupus erythematosus on significant immunosuppressive medications. Clinicians treating immunocompromised patients should be cognizant of their propensity to develop unusual infections and atypical presentations.